Effect of a Design Discharge Planning Program for Stroke Patients on Their Quality of Life and Activity of Daily Living (International Journal of Studies in Nursing, 2020)
Background: Stroke is a debilitating neurological disorder, which causes multiple physical and psychosocial challenges to people surviving a stroke. Effective discharge planning program is an active process beginning in hospitalization care and has a goal of returning to the community and aims at assisting the patients to recapture their functional independence and to return to an active and productive lifestyle. Aim: was to evaluate effect of a design discharge planning program for stroke patients on their quality of life and activity of daily living. Research design: Quasi experimental design was utilized to fulfill the aim of this study. Setting: The study was conducted at the stroke department and stroke outpatient clinics affiliated to Benha University Hospital. Sample: A convenience sample of 50 patients admitted at the above mentioned setting and diagnosed with stroke. Tools: Three tools were used: I-Patients Interviewing questionnaire sheet; II-Stroke Specific Quality of Life Scale and III- Barthel Index for Activities of Daily Living. Results: the present study revealed that (a) the mean total and subtotal knowledge scores of stroke patients were increased immediately after implementing a design discharge planning program with statistical significant difference compared to pre implementation. (b) The mean total and subtotal quality of life scores were higher after implementing discharge planning program with a high statistical significant difference compared to pre implementation. (c) The mean total and subtotal activity of daily living scores were higher after implementing discharge planning program with a high statistical significant difference compared to pre implementation. (d) There were a positive correlation between patients' knowledge, quality of life and activity of daily living with a statistical significant difference. So, all research hypotheses of the study were supported. Conclusion: Applying a design discharge planning program had statistically significant improvement on knowledge, quality of life and activity of daily living for studied patients. Recommendations: replication of this study on a larger probability sample and evaluating its impact on health outcomes among stroke patients.